The Erice 58 Charter on ‘The health of migrants. An equity challenge for the public health system’ - Marceca, M.; Fara, G. M.; Giammanco, G.; Signorelli, C.; Vitale, F.; Declich, S.; Tosti, M. E.; Fabiani, M.; Mazzucco, W.; Giorgi Rossi, P.; Barretta, P.; Affronti, M.; et al. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
The Erice 58 Charter titled “The Health of Migrants: a Challenge of Equity for the Public Health System”, was unanimously approved at the conclusion of the 58th Residential Course of the School of Epidemiology and Preventive Medicine ‘Giuseppe D’Alessandro’ entitled “The Health of Migrants: a Challenge of Equity for the Public Health System. Epidemiological, clinical-relational, regulatory, organisational, training and public communication aspects at international, national and local level’, which took place from 28 March to 2 April 2022 in Erice (Sicily, Italy), at the ‘Ettore Majorana’ Foundation and Centre for Scientific Culture. The Course was promoted by the Italian Society of Migration Medicine (S.I.M.M.) and the Italian Society of Hygiene, Preventive Medicine and Public Health (SItI), with the collaboration and patronage of the Istituto Superiore di Sanità (ISS). 72 learners participated (mainly resident doctors in ‘Hygiene and Preventive Medicine’ but also other health service professionals), whose average age was 37 years; on the basis of territorial origin, 13 of the 20 Italian regions were represented. During the intense learning experience, which consisted of 18 frontal lessons (with 20 lecturers from the bio-medical, socio-anthropological and journalistic fields) and 7 working group sessions (supported by 4 classroom tutors in addition to the lecturers) in ‘blended learning’ mode, the various dimensions and critical issues related to the possibility of guaranteeing truly inclusive health policies for foreigners/migrants, throughout the country, were identified and discussed from an ‘Health Equity’ perspective. This enabled a small editorial group to draw up the basic document that, in the last session of the Course, was discussed and modified by all participants into the version of the ‘Erice 58 Charter’ presented here.